Operating Systems - Dhamdhere, D. ([S.l.] : Science Engineering & Math, 2015)
After authoring a best-selling text in India, Dhananjay Dhamdhere has written Operating Systems, and it includes precise definitions and clear explanations of fundamental concepts, which makes this text an excellent text for the first course in operating.
Kindle eBook.
Keywords: Operating systems